(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. All’origine (antropologica) del problema: tra scandalo e linciaggio rituale - 2. Competenza confessionale (legalmente pacifica) sull’accusa - 3. (intermezzo) Parallelismi tra linciaggio e scomunica - 4. (segue) Natura giuridica dell’intervento di Pilato. Una lezione di laicità. Jesus before Pilate. Procedural remarks on a case of legalisation of ecclesiastical lynching ABSTRACT: The Author wants to reconsider the trial of Jesus through a double critical grid: that of elimination by lynching of those who, by causing scandals, have cracked, regardless of any guilt, the certainties of the group (model dating back to immemorial times, and expression of pagan myths), and that of the execution of the death sentence issued by the great Sanhedrin of Jerusalem against the Nazarene, subject to adequate control by the Roman praetor (limited, however, only to the conditions of its admissibility by the imperial system). The discussion proceeds by underlining the full autonomy in merit of the confessional verdict, which the execution power accessed as a mere formal verification of the existence of conditions of public order considered indispensable by the State system. On the side-lines, the Author takes the opportunity to highlight how these precautions have become less and less renounceable over time, in face of the recurrent ecclesiastical claim to re-propose in new forms the ancestral logic of the ritualized lynching of discuting members.